Exploring the influence of novelty and authenticity in wine consumption: the moderating effect of regionality and price. Issue 2 (4th December 2020) - Barber, Matthew; Sung, Billy; Lee, Sean; Cheah, Isaac
Abstract : Purpose: The consumption of wine is influenced by seemingly contradictory antecedents such as perceived authenticity and novelty. This paper aims to explore the influence novelty and authenticity have on wine consumption, in the context of the moderating variables of regionality (i.e. single and multi-region wines) and price (low and high). The research attempts to further understand wine consumption by establishing a conceptual model built on existing wine literature. Design/methodology/approach: To address the hypotheses and research questions, a panel of 658 consumers who regularly purchased wines produced by the Australian wine industry were recruited. These participants completed a self-administered questionnaire containing stimuli to measure perceived authenticity, perceived novelty, perceived quality, attitudes and purchase intent towards a wine manipulated to have a low vs high price level, as well as single vs multi-regional label. To examine these variables, the study conducted a confirmatory factor analysis (CFA) to confirm the dimensionality of the constructs and structural equation modeling with both path and multi-group analyses to investigate the hypothesised relationships. Findings: The findings revealed that both authenticity and novelty simultaneously influence perceived quality. Additionally, it was acknowledged that there is no significant difference in wine consumption between single and multi-regional wines; reinforcing current trends of collaboration within the wine industry. Finally, the results also showed that price does moderate wine consumption; revealing ideal prices for wine with particular regional branding strategies. Originality/value: The current research is the first to show that authenticity and novelty simultaneously and positively influence consumer's perceived quality of Australian wine. The findings are also the first to show that consumer evaluation of single and multi-origin wines was positive and yielded no significant difference, suggesting that branding wines with multi-origins or multi-region do not change consumers' perception.